The Implementation of “ Discovery Channel Video” to Teach Writing Ability of Students About Descriptive Text (RETAIN, 2014)
Abstrak Menulisadalahrepresentasi visual daripikiran, perasaan, dan ide-ide denganmenggunakansimbol-simbolsistembahasapenulis 'untuktujuankomunikasiataurekaman.Dalampengajaranmenulis, guru harusmendorongsiswauntukmeningkatkan / kemampuannyaberbicarapadanya.Studiinifokuspadapenggunaan "Discovery Channel" Video untukmengajarmenulisteksdeskriptif."Discovery Channel" Video yang video tertentu yang terdiridarideskripsisingkattentangkarakteristikumumbeberapahal.Disampingpenerapan media tersebut, penelitijugamendeskripsikanresponsiswadalampenggunaan media tersebutdalammenulisteks narrative.Penelitianiniadalah descriptive qualitative denganmenggunakancatatanlapangan, checklist observasi, danangketsebagai instrument untukmengumpulkan data.Penelitianinidilakukan di SMPN 50 Surabaya padasiswakelas IIIV- B yang terdiridari 38 siswapadatigapertemuan.Berdasarkan data, penggunaan "Discovery Channel" Video untukmengajarmenulisteksdeskriptifberhasilkarenasiswadapatmenulisteksdeskriptifdenganbaiksetelahmerekamenyaksikan "Discovery Channel" video. Kemampuanmenulismerekameningkat di pertemuankeduadanselanjutnya di pertemuanketigaSebagai saran, guru bahasaInggrisdapatmenggunakan "Discovery Channel" video sebagai Media alternatifuntukmengajarmenulisteksdeskriptifuntukdelapansiswakelas SMP. Kata Kunci: Video Discovery Channel, menulis, teksdeskriptif Abstrack Writing is a visual representation of thoughts, feelings, and ideas using symbols of the writers’ language system for the purpose of communication or recording. In the teaching writing, the teacher must encourage the student to increase his/her speaking ability.This study focus on the use of “Discovery Channel” video to teach writing descriptive text. “Discovery Channel” video which specific video that consist of short description about general characteristic some specific thing. Besides the implementation the media, the researcher also describes the students’ responses toward the use of the media to write narrative text. This research was a descriptive qualitative which used field note, observation checklist, and questionnaires as instruments to gather the data. This reseach conduct at SMPN 50 Surabaya in the eight grade students of IIIV- B which consist of 38 students on three meetings. Based on the data, the use of “Discovery Channel” video to teach writing descriptive text was successful because the students can write descriptive text well after they watched the “Discovery Channel” video. Their writing ability increased in second meeting and furthermore in third meeting As suggestion, English teacher can use “Discovery Channel” video as alternative Media to teach writing descriptive text to the eight grade students of junior high school. Keyword: Discovery Channel video, writing, descriptive text